Ultrasonographic verification of hepatic hydatidosis in a female dromedary camel: a case report - THARWAT, Mohamed; MOGHAZY, Hazem M EL; OIKAWA, Shin (Journal of Veterinary Medical Science, 2023)
This report describes for the first time, the antemortem diagnosis of hydatidosis in dromedary camel based on the WHO informal working groups on echinococcosis guidelines of echinococcosis classification. The case was admitted at the University Veterinary Hospital, Qassim University, Saudi Arabia, with a history of progressive weight loss and decreased appetite for the past 4 months. Alterations in hematobiochemical parameters included leukopenia, neutropenia, decreased hematocrit percent, red blood cells count and hemoglobin concentration, hypoproteinemia, hypoalbuminemia, hyperglobulinemia, hyperglycemia and azotemia. Ultrasonographically, multiple cysts were imaged within the hepatic tissue containing anechoic fluid and fibrin tags. Ultrasound-guided aspiration of a cyst revealed a clear non-turbid fluid. Ultrasonographic diagnostic is recommended for the work-up of cystic lesions of camel liver suspected to be due to Echinococcus granulosus.